Capacity of recombinant gamma interferon to activate macrophages for Salmonella-killing activity. - Kagaya, K (1989)
The ability of recombinant gamma interferon (rIFN-gamma) to activate macrophages for Salmonella-killing activity was kinetically examined in relation to phagosome-lysosome fusion and H2O2 generation. Resident peritoneal macrophages of BALB/c mice incubated with 10(2) to 10(3) U of rIFN-gamma per ml for 12 h exhibited enhanced bactericidal activity against Salmonella typhimurium, although H2O2 generation was unaltered. In contrast, macrophages incubated with equal doses of rIFN-gamma for 48 h showed both an enhanced Salmonella-killing activity and an increased generation of H2O2. To evaluate Salmonella-killing activities of macrophages, intracellular bacteria were assayed at 0, 2, and 8 h after infection. During the initial 2 h of infection, 12-h-activated macrophages, as well as the unstimulated control macrophages, showed a decline in bacterial population at the same rate. Over the next 6 h of infection, however, the number of viable bacteria in activated macrophages remained unchanged, whereas the number of bacteria in control macrophages significantly (P less than 0.05) increased. Similar results were obtained in 48-h-activated macrophages. On the other hand, macrophages incubated with 10 to 10(3) U of rIFN-gamma exhibited enhanced fusion of lysosomes to Salmonella-containing phagosomes in both the 12-h- and 48-h-stimulated stages. Moreover, when 48-h-activated macrophages were incubated concomitantly with superoxide dismutase and catalase, Salmonella-killing activity was not affected. These results indicate that rIFN-gamma per se is able to activate peritoneal macrophages to induce Salmonella-killing activity and suggest that increased phagosome-lysosome fusion followed by an oxygen-independent killing mechanism is primarily responsible for the enhanced Salmonella-killing activity in rIFN-gamma-activated macrophages.